Sln. nocój in njegove vzporednice v slovanskih jezikih - Šivic-Dular, Alenka (Slavistična revija, 1982)
The common Slovene adverb nocój 'tonightm this evening' is derived from the temporal use of the un prepositioned instrumental singular *noco, 'at/by night'. Due to its identity with the West Slavic (still paradigmatical) form *noco 'same', i.e. with the contracted Proto-Slavic ending 'jo, it must be considered a trace of an old West migration towards the Balkans.
Keywords: primerjalno slovansko jezikoslovje; prislov; slovanski jeziki; slovenščina